Tradisi Tedhak Siten Masyarakat Jawa Ditinjau dari Ajaran Islam Studi Kasus Desa Parbalongan, Kecamatan Tanah Jawa, Kabupaten Simalungun - Addini, Syahira; Harahap, Aprilinda M.; Zulkarnain, Zulkarnain (ANWARUL, 2023)
This research is motivated by the many traditions that exist in Indonesia, especially the Javanese. Being one of the traditions of the Javanese people, namely the Tedhak Siten tradition. Of course, an area like Parbalogan Village has challenges between culture and religion. So, it can be observed directly the procession and Islamic view of the Tedhak Siten tradition. The formulation of the research problem is first, explaining how the procession of the Tedhak Siten tradition is. Second, an analysis of Islamic views on Tedhak Siten in the people of Parbalogan Village. This study aims to explore and find out how the Tedhak Siten tradition procession in Parbalongan Village and how the Islamic view of the Tedhak Siten tradition in Parbalogan Village. This research is a qualitative research oriented to field research (Library Research) using an Anthropological approach, and the theory is Ethnicity. Sources of data generated from the results of interviews, observations, and documentation. This study aims to explore and find out how the procession of the Tedhak Siten tradition and how the Islamic view of the Tedhak Siten tradition in Parbalogan Village. The results of this study are that the Tedhak Siten tradition is considered as the salvation of the Javanese people which has existed since the ancestors, which means that the child who enters 7 months is just starting to walk. The procession of the Tedhak Siten tradition consists of various series, each of which has a good meaning for the child for his future. So that the results of the research obtained can be concluded that First, the procession of the Tedhak Siten tradition is a tradition of the ancestors for the child who starts walking, Second, the Tedhak Siten tradition must be a child aged 7 months or pitu eight which can be started by the Tedhak Siten tradition, Third, in the view of In the Islamic religion, this tradition is still permissible because it is considered a form of gratitude to God and in each of its sequences it has a meaning that contains the values of Islamic teachings.